2001
DOI: 10.1093/ajcn/73.2.374s
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic bacteria in fermented foods: product characteristics and starter organisms

Abstract: Probiotic bacteria are sold mainly in fermented foods, and dairy products play a predominant role as carriers of probiotics. These foods are well suited to promoting the positive health image of probiotics for several reasons: 1) fermented foods, and dairy products in particular, already have a positive health image; 2) consumers are familiar with the fact that fermented foods contain living microorganisms (bacteria); and 3) probiotics used as starter organisms combine the positive images of fermentation and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
256
0
45

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(305 citation statements)
references
References 21 publications
4
256
0
45
Order By: Relevance
“…Isto porque, além destes produtos possuírem grande aceitação pelo público em geral e apresentarem excelente valor nutritivo, são veículos em potencial para o consumo de probióticos (ANTUNES et al, 2007). Segundo Heller (2001), os consumidores estão familiarizados com o fato de que alimentos fermentados podem apresentar microrganismos vivos.Apenas iogurtes e leites fermentados contendo culturas probióticas devem ser considerados funcionais (ANTUNES; CAZETTO;CARDELLO, 2004). No entanto, os consumidores em geral não sabem distinguir quais são os produtos lácteos funcionais.…”
unclassified
See 1 more Smart Citation
“…Isto porque, além destes produtos possuírem grande aceitação pelo público em geral e apresentarem excelente valor nutritivo, são veículos em potencial para o consumo de probióticos (ANTUNES et al, 2007). Segundo Heller (2001), os consumidores estão familiarizados com o fato de que alimentos fermentados podem apresentar microrganismos vivos.Apenas iogurtes e leites fermentados contendo culturas probióticas devem ser considerados funcionais (ANTUNES; CAZETTO;CARDELLO, 2004). No entanto, os consumidores em geral não sabem distinguir quais são os produtos lácteos funcionais.…”
unclassified
“…Isto porque, além destes produtos possuírem grande aceitação pelo público em geral e apresentarem excelente valor nutritivo, são veículos em potencial para o consumo de probióticos (ANTUNES et al, 2007). Segundo Heller (2001), os consumidores estão familiarizados com o fato de que alimentos fermentados podem apresentar microrganismos vivos.…”
unclassified
“…Bifidobacteria and lactobacilli are the most commonly used probiotics in fermented dairy products. To date, probiotic strains that have been isolated and widely used in commercial products include Lactobacillus acidophilus , Lactobacillus casei , Lactobacillus rhamnosus, and Bifidobacterium bifidum (Heller, 2001). Studies have shown that L. casei could help to prevent enteric infections and stimulate immune responses in an animal model (Perdigon, Alvarez, Rachid, Agüero, & Gobbato, 1995), while supplementation of L .…”
Section: Introductionmentioning
confidence: 99%
“…Entre os fatores que influenciam a viabilidade das bactérias probióticas no produto elaborado podem ser destacados o estado fisiológico dos organismos probióticos adicionados, as condições físicas de estocagem (tempo, temperatura), a composição quími-ca do produto no qual os microrganismos serão adicionados (acidez, conteúdo de carboidratos utilizáveis, fontes de nitrogênio, conteúdo mineral, atividade de água, conteúdo de oxigênio) e possíveis interações dos probióticos (bacteriocinas, antagonismo, sinergismo) com outras culturas starter (Heller, 2001).…”
Section: Introductionunclassified